Pengembangan Learning Management System Terintegrasi Project Based Learning Untuk Mendukung Hasil Belajar Pada Materi Konfigurasi Routing(Studi Kasus Siswa Kelas Xi Tjkt Smkn 1 Kediri) - Husna Lathifunisa Arif; Harun Al Rosyid (CV. SINAR HOWUHOWU, 2026)
This study is motivated by students' low learning outcomes in the subject matter, caused by suboptimal teaching methods and a lack of interactive media to support independent networking practice. This research aims to develop a Moodle-based Learning Management System (LMS) named